Comparison of prognostic and predictive impact of genomic or central grade and immunohistochemical subtypes or IHC4 in HR+/HER2- early breast cancer: WSG-AGO EC-Doc Trial - Gluz, O.; Liedtke, C.; Huober, J.; Peyro-Saint-Paul, H.; Kates, R. E.; Kreipe, H. H.; Hartmann, Arndt; Pelz, E.; Erber, Ramona; Mohrmann, S.; Moebus, V.; Augustin, D.; et al. (Annals of Oncology, 2016)
Potential prognostic and predictive markers in early, intermediate-risk breast cancer (BC) include histological grade, Ki-67, genomic signatures, e.g. genomic grade index (GGI), and intrinsic subtypes. Their prognostic/predictive impact in hormone receptor (HR: ER and/or PR) positive/HER2- BC is controversial. WSG-AGO EC-Doc demonstrated superior event-free survival (EFS) in patients with 1-3 positive lymph node receiving epirubicin/cyclophosphamide-docetaxel (EC-Doc) versus 5-fluoruracil/epirubicin/cyclophosphamide (FEC).In a representative trial subset, we quantify concordance among factors used for clinical chemotherapy indication. We investigate the impact of central histology (n = 772), immunohistochemistry for intrinsic subtyping and IHC4, and dichotomous (GG) or continuous (GGI) genomic grade (n = 472) on patient outcome and benefit from taxane chemotherapy, focusing on HR+/HER2- patients (n = 459).Concordance of local grade (LG) with central (CG) or genomic grade was modest. In HR+/HER2- patients, low (GG-1: 16%), equivocal (GG-EQ: 17%), and high (GG-3: 67%) GG were associated with respective 5-year EFS of 100%, 93%, and 85%. GGI was prognostic for EFS within all LG subgroups and within CG3, whereas IHC4 was prognostic only in CG3 tumors.In unselected and HR+/HER2- patients, CG3 and luminal-A-like subtype entered the multivariate EFS model, but not IHC4 or GG. In the whole population, continuous GGI entered the model [hazard ratio (H.R.) of 75th versus 25th = 2.79; P = 0.01], displacing luminal-A-like subtype; within HR+/HER2- (H.R. = 5.36; P < 0.001), GGI was the only remaining prognostic factor.In multivariate interaction analysis (including central and genomic grade), luminal-B-like subtype [HR+ and (Ki-67 >=20% or HER2+)] was predictive for benefit of EC-Doc versus FEC in unselected but not in HR+/HER2- patients.In the WSG-AGO EC-Doc trial for intermediate-risk BC, CG, intrinsic subtype (by IHC), and GG provide prognostic information. Continuous GGI (but not IHC4) adds prognostic information even when IHC subtype and CG are available. Finally, the high interobserver variability for histological grade and the still missing validation of Ki-67 preclude indicating or omitting adjuvant chemotherapy based on these single factors alone.The WSG-AGO/EC-Doc is registered at ClinicalTrials.gov, NCT02115204.
EVALuna2:6775